QAWAID FIQHIYYAH SEBAGAI LANDASAN ETIKA PENGGUNAAN MEDIA SOSIAL DALAM PERSPEKTIF HUKUM ISLAM - Azhari, Muhammad Iqbal (STAI ALHIKMAH Jakarta, 2024)
AbstractThis article discusses the application of qawaid fiqhiyyah as an ethical foundation for social media usage among Muslims, focusing on the understanding and implementation of Islamic law principles in digital contexts. The unique contribution of this research lies in emphasizing the importance of qawaid fiqhiyyah in guiding the behavior of social media users, as well as addressing the challenges and opportunities faced. The methodology employed is library research, which includes a literature analysis relevant to describing social media user behavior. The findings indicate that although there is awareness of the importance of ethics in social media use, many users still lack understanding and implementation of qawaid fiqhiyyah principles, such as tabayyun (information verification) and maslahah (general welfare). These findings highlight the need for better education regarding digital-based Islamic ethics, along with the active roles of families and communities in educating younger generations. By applying qawaid fiqhiyyah, it is hoped that social media users can contribute to creating a more positive and productive environment while strengthening their identity as Muslims in the digital age. This research provides practical implications by encouraging the development of clear ethical guidelines for social media use in accordance with Islamic values. AbstrakArtikel ini membahas penerapan qawaid fiqhiyyah sebagai landasan etika dalam penggunaan media sosial di kalangan umat Muslim, dengan fokus pada pemahaman dan implementasi prinsip-prinsip hukum Islam dalam konteks digital. Kontribusi unik penelitian ini terletak pada penekanan pentingnya qawaid fiqhiyyah dalam membimbing perilaku pengguna media sosial, serta tantangan dan peluang yang dihadapi. Metodologi yang digunakan adalah penelitian pustaka (library research) yang mencakup analisis literatur relevan untuk menggambarkan perilaku pengguna media sosial. Hasil penelitian menunjukkan bahwa meskipun terdapat kesadaran akan pentingnya etika dalam penggunaan media sosial, banyak pengguna masih kurang memahami dan menerapkan prinsip-prinsip qawaid fiqhiyyah, seperti tabayyun (verifikasi informasi) dan maslahah (manfaat umum). Temuan ini menekankan perlunya pendidikan yang lebih baik mengenai etika digital berbasis Islam serta peran aktif keluarga dan masyarakat dalam mendidik generasi muda. Dengan menerapkan qawaid fiqhiyyah, diharapkan pengguna media sosial dapat berkontribusi pada lingkungan yang lebih positif dan produktif, sekaligus memperkuat identitas Muslim di era digital. Penelitian ini memberikan dampak praktis dengan mendorong pengembangan pedoman etika yang jelas dalam penggunaan media sosial sesuai dengan nilai-nilai Islam.